2021
DOI: 10.1111/febs.15734
|View full text |Cite
|
Sign up to set email alerts
|

The action of hyaluronan in functional properties, morphology and expression of matrix effectors in mammary cancer cells depends on its molecular size

Abstract: Breast cancer constitutes a heterogeneous disease. The expression profiles of estrogen receptors (ERs), as well as the expression patterns of extracellular matrix (ECM) macromolecules, determine its development and progression. Hyaluronan (HA) is an ECM molecule that regulates breast cancer cells' properties in a molecular size-dependent way. Previous studies have shown that 200-kDa HA fragments modulate the functional properties, morphology, and expression of several matrix mediators of the highly metastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 133 publications
0
6
0
Order By: Relevance
“…Through its binding to the receptor CD44, HA regulates intracellular signaling pathways and cell functional properties in a size-dependent manner [ 26 ]. Recent studies have shown the role of HA fragments of different molecular size in modulating breast cancer cells proliferation, migration, and invasion [ 24 , 25 ]. Furthermore, treatment with such HA fragments results in significant alterations in the morphology and aggressive phenotype of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through its binding to the receptor CD44, HA regulates intracellular signaling pathways and cell functional properties in a size-dependent manner [ 26 ]. Recent studies have shown the role of HA fragments of different molecular size in modulating breast cancer cells proliferation, migration, and invasion [ 24 , 25 ]. Furthermore, treatment with such HA fragments results in significant alterations in the morphology and aggressive phenotype of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on its molecular size, HA exerts different biological functions and regulates specific cellular behavior. For instance, HA fragments of <10, 30, and 200 kDa affect breast cancer cells’ functional properties and morphology, as well as the expression patterns of several molecules in a size-dependent manner [ 24 , 25 ]. Moreover, high molecular weight (HMW) HA is known for its anti-inflammatory, anti-angiogenic, and anti-proliferative properties [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…HMWHA shows anti‐angiogenic, immune suppressive, and anti‐inflammatory activities, and induces tissue reparative processes as described in wound healing [242]. In an opposite fashion, the fragments of HA, called oligosaccharides when < 200 kDa, show the capacity to modify the expression of a variety of genes (such as MMPs, syndecan‐4, HPSE) to induce inflammatory processes as well as angiogenesis throughout their interactions with specific receptors [29,243–245] (Fig. 3).…”
Section: Gags: the Sweet Regulatory Partners Of Ecmmentioning
confidence: 99%
“…HA oligosaccharides promote angiogenesis which brings more nutrients to the tumor and facilitates systemic spread. Indeed, it has been demonstrated that the effects of HA in mammary cancer depend on its molecular size as well as the type of estrogen receptor (ERα/β) expressed [19][20][21].…”
Section: Proteoglycans and Glycosaminoglycansmentioning
confidence: 99%